Networking and adapting their way forward: Women heads of large, K-12 independent schools and their leadership literacies - Flaxman, Jessica R. (Frontiers in Education, 2023)
Gender disparity at the leadership level of large (defined by the National Association of Independent Schools as >700 students) K-12 independent schools is a critical and persistent issue in the ongoing effort to foster equity and justice in historically white and male-led independent schools in the United States. Since 2009, the number of women leading all independent schools has increased from 31% to 41% in 2021 (Rowe, 2021). However, while a greater number of women lead independent schools today than in years past, they more often achieve the headship in small and K-8 schools and remain less likely (22%) to achieve headship of large (>700) independent schools (NAIS DASL, Heads Gender, 2020). Using mixed-methods research including a quantitative survey of 30 of the 45 women leading large, K-12 independent schools in 2020; qualitative follow-up interviews; and analysis of exemplary “leader communications” from the crisis/pandemic school year, this study identifies the role of networking and adaptability literacies in moderating gender bias in the leadership pipeline.